The Relationship between English Proficiency and Academic Achievement of Indonesian EFL Postgraduate Students - Anit Pranita Devi (English Language Education Department, Universitas Majalengka, 2023)
There is still a debate about using English proficiency in determining one's academic success or access to an opportunity. Hence, research on the correlation of language proficiency and academic achievement is urgently needed. This study attempted to investigate the relationship between Indonesian postgraduate students’ English language proficiency and their academic achievement. To achieve the objective, 54 male and female postgraduate students majoring in English education at a university in Bandung were involved as the sample. Students’ language proficiency was seen from their Test of English as a Foreign Language (TOEFL) scores and their grade point average (GPA) was used to indicate their academic achievement. All data were analyzed through manual computation of Pearson Product-moment correlation. The result revealed that there is a significant positive linear correlation between English language proficiency and academic achievement. This result suggests that as the English proficiency increases, so does academic achievement. The results are expected to provide insight in understanding whether English language proficiency can increase academic success, especially in educational settings where English is the primary medium of instruction.